Assessing the risk of viral infection from gases and plumes during intra‐abdominal surgery: a systematic scoping review. Issue 10 (17th August 2020) - Gavin, Dominic J.; Wilkie, Bruce D.; Tay, Jia; Loveday, Benjamin P. T.; Furlong, Timothy; Thomson, Benjamin N. J.
Abstract: Background: The aim of this study was to identify the current evidence regarding the risk of acquiring viral infections from gases or plumes during intra‐abdominal surgery. Peritoneal fluids may contain cellular material and virus particles. Electrocautery smoke and plumes from energy devices may aerosolize harmful substances and viral particles. Insufflation and desufflation during laparoscopic surgery may also aerosolize and distribute biological material. A systematic scoping review was performed to assess the evidence and inform safe surgical practice. Methods: A systematic search of the PubMed and Medline databases was undertaken until June 2020, observing Preferred Reporting Items for Systematic Reviews and Meta‐Analyses methodology, to identify articles associating viral infection of operating room staff from surgical gases and plumes. All evidence levels were included. The search strategy utilized the search terms 'surgery', 'laparoscopy', 'laparoscopic' 'virus', 'smoke', 'risk', 'infection'. Results: The literature search identified 74 articles. Eight articles relevant to the subject of this review were included in the analysis, two of which specifically related to intra‐abdominal surgery. Of the remaining six, four involved gynaecological surgery and two were in‐vitro studies. No evidence that intra‐abdominal surgery was associated with an increased risk of acquiring viral infections from exsufflated gas or smoke plumes was identified. Conclusion: There is currently no evidence that respiratory viruses can be found in the peritoneal fluid. Whilst there is currently no evidence that desufflated carbon dioxide or surgical smoke plumes present a significant infectious risk, there is not a wealth of literature to inform current practice. Further clinical research in this area is required. Abstract : There is concern regarding the risk of viral transmission via surgical smoke. We performed a systematic scoping review and found that there is little evidence that virus particles can be transmitted via surgical plumes during intra‐abdominal surgery.